Pengaruh Kelengkapan Produk, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Toko Serba Ada Sahabat Ilmu Gringging Kediri - Abdiansyah, Gogot; Pramutoko, Bayu; Sholihin, Ustadus (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of product completeness, price, and service quality on purchasing decisions at Sahabat Ilmu Department Store in Gringging Kediri. The research employs a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 99 respondents selected using accidental sampling. Data analysis was conducted using SPSS, including validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results indicate that product completeness and service quality have a positive and significant effect on purchasing decisions, while price does not show a significant effect. Simultaneously, product completeness, price, and service quality significantly influence purchasing decisions, with a determination coefficient of 84.5 percent. These findings suggest that consumer purchasing decisions in the retail sector are more strongly driven by product availability and service quality than by price considerations. The managerial implication highlights the importance of maintaining comprehensive product assortments and improving service quality to enhance consumer purchasing decisions.